Making Schools Work : New Evidence on Accountability Reforms - Bruns, Barbara (World Bank, 2012)
This volume is a systematic stock-taking of the evidence on school accountability reforms in developing countries. It provides a measured and insightful review and assessment of the results of a variety of approaches that developing countries are experimenting with in their quest for better schools. It is not the final word on the subject, but will hopefully contribute to better policy choices, grounded in the evidence currently available. This book is about the threats to education quality that cannot be explained by lack of resources. It focuses on publicly financed school systems and the phenomenon of service delivery failures: cases where programs and policies that increase the inputs to education fail to produce effective delivery of services where it counts-in schools and classrooms. It documents what authors know about the extent and costs of service delivery failures in public education in the developing world. And it further develops aspects of the conceptual model posited in the World development report 2004: that a root cause of low-quality and inequitable public services-not only in education-is the weak 'accountability' of providers to both their supervisors and their clients (World Bank 2003). The central focus of this book, however, is a new story. It is that developing countries are increasingly adopting innovative strategies to attack these issues.